Site-specific backbone amide (15)N chemical shift anisotropy tensors in a small protein from liquid crystal and cross-correlated relaxation measurements - Yao, Lishan (2010)
Site-specific (15)N chemical shift anisotropy (CSA) tensors have been derived for the well-ordered backbone amide (15)N nuclei in the B3 domain of protein G (GB3) from residual chemical shift anisotropy (RCSA) measured in six different mutants that retain the native structure but align differently relative to the static magnetic field when dissolved in a liquid crystalline Pf1 suspension. This information is complemented by measurement of cross-correlated relaxation rates between the (15)N CSA tensor and either the (15)N-(1)H or (15)N-(13)C′ dipolar interaction. In agreement with recent solid state NMR measurements, the (15)N CSA tensors exhibit only a moderate degree of variation from averaged values, but have larger magnitudes in α-helical (−173 ± 7 ppm) than in β-sheet (−162 ± 6 ppm) residues, a finding also confirmed by quantum computations. The orientations of the least shielded tensor component cluster tightly around an in-peptide-plane vector that makes an angle of 19.6±2.5° with the N-H bond, with the asymmetry of the (15)N CSA tensor being slightly smaller in α-helix (η=0.23±0.17) than in β-sheet (η=0.31±0.11). The residue-specific (15)N CSA values are validated by improved agreement between computed and experimental (15)N R(1ρ) relaxation rates measured for (15)N-{(2)H} sites in GB3, which are dominated by the CSA mechanism. Use of residuespecific (15)N CSA values also results in more uniform generalized order parameters, S(2), and predicts considerable residue-by-residue variations in the magnetic field strengths where TROSY line narrowing is most effective.